Evaluation of the Consolidation Parameters Obtained from Laboratory Tests for Numerical Modeling of Improved Soft Soil Using PVD at Semarang - Demak Toll Road, Indonesia - Sari, Undayani Cita; Wardani, Sri Prabandiyani Retno; Muntohar, Agus Setyo; Partono, Windu (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
The consolidation analysis becomes complicated when conducted on varying layers of soil. To simplify and solve these problems, designers often employ Finite Element Method (FEM) modeling, a widely used technique for analyzing geotechnical issues. However, many limitations associated with this method can lead to model results that do not accurately reflect actual conditions. Consequently, the consolidation settlement analysis during design may differ from actual conditions in the field. This study examines the influence of consolidation parameters and explores how to analyze consolidation settlement using FEM for practical applications. Specifically, consolidation settlement was assessed on the Semarang-Demak toll road, which utilizes a Preloading-PVD improvement method across nine Stationing (STA) locations with varying soil layers. Numerical modeling was performed using Midas GTS NX 2021 (V.1.1) and was validated against instrumentation observation results, Settlement Plate. An evaluation using the back analysis method was conducted to investigate the impact of consolidation parameters on the accuracy of the final consolidation settlement results. The consolidation parameters reviewed are the compression index (Cc) and recompression index (Cr). The findings indicate that the Cc and Cr significantly influence the final consolidation settlement. By optimizing these consolidation parameter values, the deviation between observed results and numerical modeling for final consolidation settlement is reduced to less than 1%. Additionally, this research derived empirical equations for calculating consolidation parameters based on the Liquid Limit, a fundamental laboratory test. The results of this study can be proposed to analyze consolidation settlement using FEM modeling for soft clay to stiff clay, providing valuable insights for practical applications.